The Value of Prestige on the Father Figure in the Family Acehnese people - *Zaitun Munirah; Elly Malihah; Yadi Ruyadi (Universitas Syiah Kuala, 2022)
In Acehnese society itself, there is a system of prestige given to the head of the family at home, namely the father figure. The form of prestige is in the form of appreciation and privilege of treatment to the father. This study aims to explore the socio-cultural values embedded in Acehnese society, namely the value of prestige which is closely related to the patrilineal system. Although it is often not realized, the existence of these values is real. By using a qualitative approach in the form of a literature review study, namely a literature study that uses references from other research journals, theses, theses, books related to the prestige value of the father figure in the family. This study also relates the focus of the study to a feminist view that basically the main essence desired by women is the creation of harmony, dignity, and freedom in managing life, both from within and from outside the home. Meanwhile, in Aceh, the privileged access or advantages that women get is always related to marital status. They will get their rights if they get married, and have children. However, it is still not comparable to that obtained by the adam in the family. In conclusion, the prestige value is still embedded in the Acehnese family, but the practice is no longer the same as before